New species and records of Colurella (Rotifera: Lepadellidae) from South China, with a key to Chinese Colurella - Wei, Nan; Jersabek, Christian D.; Xu, Runlin; Yang, Yufeng (Zootaxa, 2019)
A new species of the rotifer genus Colurella (Rotifera, Monogononta, Lepadellidae), C. ovalis sp. nov., is described from four sites (an artificial pond site, a mangrove swamp site, a tidal creek site on Qi’ao Island and an estuarine river site in Macao) in the Pearl River Estuary, South China. The ovate lorica of the new species is similar to C. sanoamuangae Chittapun, Pholpunthin & Segers, 1999, but can easily be distinguished by asymmetric posterior lorica ends and a less elongate lorica. The eurythermal and euryhaline animal could be observed perennially in the mangrove swamp site, occasionally with high abundances.Besides, two species of uncertain taxonomic status, two new records of Colurella species for China and a key to Chinese Colurella species are also presented. [Species Zoobank url: urn:lsid:zoobank.org:act:A725658A-5364-45EC-8B5C-485B23252710]